2023
DOI: 10.1055/s-0042-1751449
|View full text |Cite
|
Sign up to set email alerts
|

From Sweet Molecular Giants to Square Sugars and Vice Versa

Abstract: This account describes our recent studies in the field of glycomimetics. Our efforts in understanding the structural basis of multivalent effects in glycosidase inhibition have led to decisive mechanistic insights supported by X-ray diffraction analyses and to the discovery of multimeric iminosugars displaying one of the largest binding enhancements reported so far for a non-polymeric enzyme inhibitor. Pushing the limits of the inhibitory multivalent effect has also driven progress in synthetic methodology. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 246 publications
(207 reference statements)
0
1
0
Order By: Relevance
“…In contrast, much less work has been performed with bifunctional glycosides. This may be explained by the fact that, if the sequential functionalization of the two reactive anomeric centers offers numerous synthetic opportunities, it also raises many challenges in terms of chemo-, regio-, and stereoselectivity. In conjunction with our continuing studies on glycomimetics, we have recently reported a convenient strategy for the synthesis of C -naphthyl ketosides by way of a reaction sequence involving hydrogen atom transfer (HAT)-mediated glycosylation of quinones with exo -glycals and BF 3 ·Et 2 O-catalyzed O → C glycoside rearrangement (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, much less work has been performed with bifunctional glycosides. This may be explained by the fact that, if the sequential functionalization of the two reactive anomeric centers offers numerous synthetic opportunities, it also raises many challenges in terms of chemo-, regio-, and stereoselectivity. In conjunction with our continuing studies on glycomimetics, we have recently reported a convenient strategy for the synthesis of C -naphthyl ketosides by way of a reaction sequence involving hydrogen atom transfer (HAT)-mediated glycosylation of quinones with exo -glycals and BF 3 ·Et 2 O-catalyzed O → C glycoside rearrangement (Scheme ). …”
Section: Introductionmentioning
confidence: 99%